Diurnal Cycling Transcription Factors of Pineapple Revealed by Genome-Wide Annotation and Global Transcriptomic Analysis. (23rd August 2017) - Sharma, Anupma; Wai, Ching Man; Ming, Ray; Yu, Qingyi
Abstract: Circadian clock provides fitness advantage by coordinating internal metabolic and physiological processes to external cyclic environments. Core clock components exhibit daily rhythmic changes in gene expression, and the majority of them are transcription factors (TFs) and transcription coregulators (TCs). We annotated 1, 398 TFs from 67 TF families and 80 TCs from 20 TC families in pineapple, and analyzed their tissue-specific and diurnal expression patterns. Approximately 42% of TFs and 45% of TCs displayed diel rhythmic expression, including 177 TF/TCs cycling only in the nonphotosynthetic leaf tissue, 247 cycling only in the photosynthetic leaf tissue, and 201 cycling in both. We identified 68 TF/TCs whose cycling expression was tightly coupled between the photosynthetic and nonphotosynthetic leaf tissues. These TF/TCs likely coordinate key biological processes in pineapple as we demonstrated that this group is enriched in homologous genes that form the core circadian clock in Arabidopsis and includes a STOP1 homolog. Two lines of evidence support the important role of the STOP1 homolog in regulating CAM photosynthesis in pineapple. First, STOP1 responds to acidic pH and regulates a malate channel in multiple plant species. Second, the cycling expression pattern of the pineapple STOP1 and the diurnal pattern of malate accumulation in pineapple leaf are correlated. We further examined duplicate-gene retention and loss in major known circadian genes and refined their evolutionary relationships between pineapple and other plants. Significant variations in duplicate-gene retention and loss were observed for most clock genes in both monocots and dicots.